A temporal analysis of the swimmers` coordination in the relay start - Peralvo-Simón, M.; Veiga, S.; Navia, J. A. (Sports Biomechanics, 2024)
The main aims of the present research were 1) to characterise the inter-subject and intra-subject timing of the preparatory movements of competitive swimmers during relay starts and 2) to relate the preparatory movements with the relay start outcome. Nine international youth swimmers performed 10 relay freestyle starts (one-step technique) filmed at 120 Hz from a lateral viewpoint. Results obtained (0.14 ± 0.10 s changeover time, 0.31 ± 0.07 s entry time, 2.59 ± 0.09 m entry distance and 0.96 ± 0.06 s time to 5 m) indicated that the longer the preparation time (from the initial position to the swimmer`s take-off), the better the changeover time, entry distance, and 5 m time. Specifically, a mixed linear model identified preparation time (p < 0.001, F (1,80.01) = 56.36), and entry distance (p = 0.008, F (1,80.01) = 7.36) as predicting variables for 5 m time. Also, faster swimmers on times to 5 m were found to be more consistent - lower levels of intra-subject variability - in 5 m (r = 0.76, p = 0.018) and changeover (r = 0.72, p = 0.029) times. In summary, the timing of the preparatory movements seems to be a key aspect to optimise relay start performances.